(untitled) (Global Journal of Science Frontier Research, 2021)
There has been a surge in the number of Foot and Mouth Disease (FMD) outbreaks in western Kenya between the years 2016 and 2018. A qualitative risk assessment was done to investigate the role played by cattle markets in maintenance of these outbreaks. The specific objective of the study was assessment of factors contributing to spread of FMD through cattle markets in Western Kenya.Both qualitative and quantitative data were collected using a semi-structured questionnaire. Additional data collection was done through focus group discussions guided by checklist questions and secondary data obtained through review of published and grey sources of literature. The World Organization for Animal Health (OIE) framework was adapted for this study. The conduct of selected cattle markets was assessed to determining the risk for release and exposure of FMD virus during cattle trade. The study shows there was high risk of spreading FMD virus through cattle marketing activities.